A Comparative Study on Fetomaternal Outcome in Patients with Meconium-stained Amniotic Fluid vs Clear Amniotic Fluid - Neha NIMBARK; Radhika PARMAR; Sonal SHAPARIA; Mittal JOSHI (Modern Medicine)
Aim: To compare and study the perinatal maternal outcome and complications in neonates in patients with meconium-stained amniotic fluid. Materials and methods: This was a randomized comparative analysis and prospective study conducted from 1st October 2021to 30th May 2022. 120 patients with meconium-stained amniotic fluid were studied for fetomaternal outcomes and compared to 120 patients with clear amniotic fluid. The patients were monitored for fetal heart rate, mode of delivery, Apgar score at 1 and 5 minutes, NICU admissions and neonatal complications. Result: An increased rate of caesarean section and operative vaginal deliveries was associated with meconium-stained amniotic fluid as compared to clear amniotic fluid. The commonest fetal abnormality seen was bradycardia in 35% of meconium-stained amniotic fluid cases. The APGAR score was less than 7 at 5 min in 5% of the meconium-stained amniotic fluid group and the major complication was birth asphyxia (18.18%) which was more in the thick MSL group (14.87%). Meconium aspiration syndrome was seen in 4 in the the MSL group and 2 in thin MSL group. NICU admission was required in 18% of cases in MSL group while 7% in the control group. The morbidity was more in the MSL group (52%) than thin MSL group (20%). Conclusion: The study proved that meconium staining of amniotic fluid affects the fetal outcome adversely.